(untitled) (Applied Biological Research, 2025)
While screening for a few novel bacterial strains capable of producing coenzyme Q10 (CoQ10), a wild-type Cereibacter sphaeroides strain was isolated and identified. To increase the production of CoQ10 by this wild-type strain, optimization of the upstream process was carried out through response surface methodology (RSM). To maximize CoQ10 synthesis, a central composite design (CCD) was used to optimize the media composition, which included sucrose, ammonium sulphate, peptone, and MgSO₄. The desirability function approach was used to determine the ideal level for each element, and CoQ10 concentrations were tracked as response variables. The results indicated that using the optimal culture composition (30 g L⁻¹ sucrose, 15 g L⁻¹ ammonium sulphate, 25 g L⁻¹ peptone, and 0.50 g L⁻¹ MgSO₄) produced an average of 8.5 mg g⁻¹ dry cell weight (DCW) of CoQ10. Regression analysis results showed that the most efficient factors in generating CoQ10 were MgSO₄ and ammonium sulphate concentrations.